Comparison of gram-negative and gram-positive hematogenous pyogenic spondylodiscitis: clinical characteristics and outcomes of treatment. Issue 1 (December 2016) - Lee, Ching-Yu; Wu, Meng-Huang; Cheng, Chin-Chang; Huang, Tsung-Jen; Huang, Tsung-Yu; Lee, Chien-Yin; Huang, Jou-Chen; Li, Yen-Yao
Abstract Background To the best of our knowledge, no study has compared gram-negative bacillary hematogenous pyogenic spondylodiscitis (GNB-HPS) with gram-positive coccal hematogenous pyogenic spondylodiscitis (GPC-HPS) regarding their clinical characteristics and outcomes. Methods From January 2003 to January 2013, 54 patients who underwent combined antibiotic and surgical therapy in the treatment of hematogenous pyogenic spondylodiscitis were included. Results Compared with 37 GPC-HPS patients, the 17 GNB-HPS patients were more often found to be older individuals, a history of cancer, and a previous history of symptomatic urinary tract infection. They also had a less incidence of epidural abscess formation compared with GPC-HPS patients from findings on magnetic resonance imaging (MRI). Constitutional symptoms were the primary reasons for initial physician visits in GNB-HPS patients whereas pain in the affected spinal region was the most common manifestation in GPC-HPS patients at initial visit. The clinical outcomes of GNB-HPS patients under combined surgical and antibiotic treatment were not different from those of GPC-HPS patients. In multivariate analysis, independent predicting risk factors for GNB-HPS included a malignant history and constitutional symptoms and that for GPC-HPS was epidural abscess. Conclusions The clinical manifestations and MRI presentations of GNB-HPS were distinguishable from those of GPC-HPS.